Turning the tide : the University of Alabama in the 1960s - Tilford, Earl H. (University Alabama Press, 2014)
"Turning the Tide is an institutional and cultural history of a dramatic decade of change at the University of Alabama set against the backdrop of desegregation, the continuing civil rights struggle, and the growing antiwar movement"--